Sarilumab reduces disease activity in rheumatoid arthritis patients with inadequate response to janus kinase inhibitors or tocilizumab in regular care in Germany. Issue 1 (1st February 2022) - Tony, Hans-Peter; Feist, Eugen; Aries, Peer Malte; Zinke, Silke; Krüger, Klaus; Ahlers, Jonas; Albrecht, Inka; Barrionuevo, Christian; Kalus, Stefanie; Burkhardt, Harald
Abstract: Objectives: The aim was to evaluate the safety and effectiveness of sarilumab in RA patients after inadequate response (IR) to janus kinase inhibitors (JAKi) and tocilizumab. Methods: The prospective, observational, 24-month single-arm PROSARA study (SARILL08661) is currently running in Germany at 96 sites. RA patients were prospectively selected at the physician's discretion according to label. This interim analysis included 536 patients over a treatment course of ≤6 months. Patients were stratified in four groups according to pretreatment before the start of sarilumab therapy: last prior treatment JAKi (JAKi-IR); last prior treatment tocilizumab (tocilizumab-IR); any other biological DMARD (bDMARD) in treatment history (bDMARD TH); and patients who had not received any bDMARDs or targeted synthetic (ts) DMARDs (b/tsDMARD naive) before. Results: For this preplanned interim analysis, 536 patients were included in the baseline population, of whom 502 patients had at least one corresponding post-baseline effectiveness assessment documented (main analysis population). In all analysed cohorts, safety was consistent with the anticipated profile of sarilumab, without new safety signals. Six months of sarilumab treatment attenuated disease activity in JAKi-IR, tocilizumab-IR, bDMARD TH and b/tsDMARD-naive patients to a very similar extent. Physical function did not change substantially over the course of treatment. Rates of premature study discontinuation were comparable between cohorts. Conclusion: Sarilumab treatment was effective in patients with IR to JAKi and tocilizumab, with an expectable safety profile and drug retention over 6 months. Confirmation of these promising results should encourage further studies on this treatment sequence, which is of high practical relevance. Study registration: Paul-Ehrlich-Institut—Federal Institute for Vaccine and Biomedics, SARILL08661.